A system study on the warehouse operations of Tupperware Brands in the Philippines Inc. - Bato, Ryna Patricia M. (Animo Repository, 2017)
For the year 2015, the actual service level hit rate in the warehouse for 2015 did not meet the target service level hit rate of 99.90% by 0.41% which corresponds to a total unmet demand in units of 67,421 boxed items and 34,237 lose items, thus incurring a loss due to interest of approximately Php899,426.33. This was considered to be the problem statement of the study. Through cause analysis and validation, the root causes were identified as the insufficient picking process time resulting to unfulfilled required number of shipping advises (SAs) and that the stocks per aisle or shelf are not monitored causing a discrepancy on the actual number of items and the recorded number of items. The solutions suggested were evaluated using the Kepner-Tregoe decision analysis (KTDA) to determine the accepted solutions for the system. Upon the evaluation of the proposed solution, the scanning process was eliminated from the outbound porcess and the picking process was reduced from 1442.85 seconds to 1090.78 seconds. Correspondingly, the increased output of SAs per hour increased by 32.28% completely eliminating the average number of unfulfilled SAs of the present system of 23.27 SAs. The development and implementation of the monitoring system is expected to recude the discrepancy on the actual number and recorded number of items from 224,978 item units to 11,248 item units. With the proposed sytem, equipment such as barcode scanners will be purchased due to the implementation of the monitoring system amounting to Php618,913.0 and total recurring costs of Php31,333.40 due to annual maintenance costs and premium pay due to sweep-checking. The total annual savings amounted to Php1,343,963.64. Wiht he cost-benefit analysis, the net present value of the implementation of the proposed system totaled to Php3,997,910.71, with a payback period of approximately 6 months.